2017
DOI: 10.1134/s0040577917110083
|View full text |Cite
|
Sign up to set email alerts
|

A concise review of pseudobosons, pseudofermions, and their relatives

Abstract: We review some basic definitions and few facts recently established for D-pseudo bosons and for pseudo-fermions. We also discuss an extended version of these latter, based on biorthogonal bases, which lives in a finite dimensional Hilbert space. Some examples are described in details.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This shows the analogy of our formalism with that in [19]. Nevertheless, there are some minor differences that should not affect the essential idea.…”
Section: Gamow States As Pseudo-bosonsmentioning
confidence: 64%
See 3 more Smart Citations
“…This shows the analogy of our formalism with that in [19]. Nevertheless, there are some minor differences that should not affect the essential idea.…”
Section: Gamow States As Pseudo-bosonsmentioning
confidence: 64%
“…We have also shown that the two families of Gamow states behave as pseudo-bosons in the sense given by Bagarello in [19]. We have constructed respective topologies on the spaces spanned by both families of Gamow states and shown that the corresponding ladder operators are continuous under these topologies.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…These equalities imply that F Φ and F ξ are biorthonormal, and, [31], that they are D-quasi bases if and only if F ϕ and F ψ are D-quasi bases. This property, useful to deduce several mathematical properties of the system, as already stated, is always true in all the physical systems where D-PBs have been shown to appear so far, [31,32]. We end this section with Tables 1 and 2 which contain several useful formulas involving all the vectors introduced in this section.…”
Section: Iii1 Deformed D-pbsmentioning
confidence: 73%